2017
DOI: 10.1002/ejhf.991
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety of intravenous cardiovascular agents in acute heart failure: results from the European Society of Cardiology Heart Failure Long‐Term Registry

Abstract: Vasodilators did not demonstrate any association with long-term clinical outcomes, while inotropes and/or vasopressors were associated with increased risk of all-cause death, mostly related to excess of in-hospital mortality in AHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
91
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 22 publications
5
91
0
3
Order By: Relevance
“…The authors concluded that vasodilators did not demonstrate any association with long‐term clinical outcomes, while inotropes and/or vasopressors were associated with an increased risk of all‐cause mortality, mainly related to an excess in in‐hospital mortality. It is of note that these results were confirmed in each of the countries participating in the registry . To minimize clinical differences amongst patients treated with or without i.v.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…The authors concluded that vasodilators did not demonstrate any association with long‐term clinical outcomes, while inotropes and/or vasopressors were associated with an increased risk of all‐cause mortality, mainly related to an excess in in‐hospital mortality. It is of note that these results were confirmed in each of the countries participating in the registry . To minimize clinical differences amongst patients treated with or without i.v.…”
mentioning
confidence: 57%
“…The second and more complex question is: ‘Why are inotropes harmful?’ In the present paper, Mebazaa et al . do not comment about the possible mechanisms that could explain the detrimental effect of inotropes in patients with acute HF .…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…246 BMS-986231, a novel second-generation nitroxyl donor with potential inotropic, lusitropic and vasodilatory effects in patients hospitalized with decompensated heart failure and reduced ejection fraction (HFrEF), was safe and had beneficial haemodynamic effects. 246 BMS-986231, a novel second-generation nitroxyl donor with potential inotropic, lusitropic and vasodilatory effects in patients hospitalized with decompensated heart failure and reduced ejection fraction (HFrEF), was safe and had beneficial haemodynamic effects.…”
Section: Medical Therapymentioning
confidence: 99%
“…Two studies, both conducted using a propensity matching approach, show the different significance of intravenous and oral therapies in patients admitted for acute HF. An analysis of 6926 patients hospitalized for acute HF in the ESC‐HF‐Long Term Registry reported that intravenous diuretics and/or vasodilators were not associated with in‐hospital or long‐term outcomes, whereas the use of intravenous inotropes and/or vasopressors was associated increased in‐hospital and long‐term mortality rates (HR 1.873, 95% CI 1.151–3.048 and HR 1.434, 95% CI 1.128–1.823, respectively) . This association between intravenous inotropes/vasopressors and outcomes was lost when only the patients discharged alive were analysed, suggesting that intravenous agents may affect only the short‐term outcomes …”
Section: Acute Heart Failure and Post‐discharge Outcomesmentioning
confidence: 99%